2014
DOI: 10.5551/jat.20123
|View full text |Cite
|
Sign up to set email alerts
|

Expression Analysis of Leukotriene-Inflammatory Gene Interaction Network in Patients with Coronary Artery Disease

Abstract: Aim: Leukotrienes are important lipid inflammatory mediators that play a pivotal role in the pathogenesis of atherosclerosis. We aimed to construct a network of interactions between leukotrienes and inflammatory biomarkers and evaluate the expression of key members of the leukotriene pathway and leukotriene-induced inflammatory molecules in patients with coronary artery disease (CAD) and healthy controls. Methods: Leukotrienes and their regulatory inflammatory molecules reported in the literature were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…LTs are lipid mediators that are derived from the 5-lipoxygenase pathway of arachidonic acid metabolism, and which modulate inflammation in pulmonary arterial hypertension ( 32 ). LTs serve a pivotal role in the pathogenesis of atherosclerosis, have a close association with CHD ( 33 ), and additionally increase oxygen free radicals involved in the development and maintenance of heart failure, which is a typical symptom of PHD ( 34 ). Due to the fact that LTs are important in IPAH, CHD and PHD, the use of agents that influence the LT pathway has potential for the use in treatment for IPAH and PHD ( 32 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LTs are lipid mediators that are derived from the 5-lipoxygenase pathway of arachidonic acid metabolism, and which modulate inflammation in pulmonary arterial hypertension ( 32 ). LTs serve a pivotal role in the pathogenesis of atherosclerosis, have a close association with CHD ( 33 ), and additionally increase oxygen free radicals involved in the development and maintenance of heart failure, which is a typical symptom of PHD ( 34 ). Due to the fact that LTs are important in IPAH, CHD and PHD, the use of agents that influence the LT pathway has potential for the use in treatment for IPAH and PHD ( 32 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the fact that LTs are important in IPAH, CHD and PHD, the use of agents that influence the LT pathway has potential for the use in treatment for IPAH and PHD ( 32 , 34 ). LTs have additionally been identified to be effective in predicting CHD ( 33 ). Functional observations including oxidation reduction, the unsaturated fatty acid biosynthetic process, the glycoprotein biosynthetic process and the eicosanoid metabolic process were additionally identified to be associated with IPAH, CHD and PHD in the current study; however, these observations require further investigation and discussion.…”
Section: Discussionmentioning
confidence: 99%
“…Selection of candidate genes : The network approach helped identify key inflammatory genes from a large panel of genes involved in the inflammatory process and the direct interactions among the genes in the leukotriene pathway 6 7 . The 18 genes prioritized for the present study are listed in Table II and include the leukotriene pathway genes, inflammatory genes and key transcription factors.…”
Section: Methodsmentioning
confidence: 99%
“…To address this, the expression of a select panel of 18 inflammatory genes was studied in patients with MetS and CAD and the association and correlation patterns of relative gene expression were compared with each other and against controls. These 18 genes were selected based on bioinformatics analysis of the inflammatory bionetwork previously carried out for gene prioritization 6 and through a selection of highly networked leukotriene-induced inflammatory genes described elsewhere 7 .…”
mentioning
confidence: 99%
“…IL-8 production remains elevated for an extended period during acute inflammation, whereas other inflammatory cytokines are cleared within a few hours (DeForge et al, 1992;Shebuski and Kilgore, 2002). Liu et al (1997) suggested that IL-8 contributes to the recruitment of T lymphocytes and smooth muscle cells to the subendothelial space and has a major role in the formation of atherosclerotic lesions, whereas Nair et al (2014) showed that IL-8 gene expression is a predictor of cardiovascular risk. Therefore, IL-8 may play a role in the pathogenesis of atherosclerosis, and thus appears to be associated with the development of CAD.…”
Section: Discussionmentioning
confidence: 99%